Single nucleotide polymorphisms in PNPLA3, ADAR-1 and IFIH1 are associated with advanced liver fibrosis in patients co-infected with HIV-1//hepatitis C virus. (1st December 2021) - Franco, Sandra; Horneros, Judith; Soldevila, Laura; Ouchi, Dan; Galván-Femenía, Iván; de Cid, Rafael; Tenesa, Montserrat; Bechini, Jordi; Perez, Ricardo; Llibre, Josep M.; Clotet, Bonaventura; Tural, Cristina; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Nonalcoholic fatty liver disease (NAFLD), insulin resistance and liver fibrosis are prevalent in individuals co-infected with HIV type 1 (HIV-1)/hepatitis C virus (HCV), even after HCV eradication. Our aim was to evaluate single nucleotide polymorphisms (SNPs) associated with advanced liver fibrosis in HIV-1/HCV co-infected patients. Design/methods: In a cohort of 102 participants, we genotyped 16 SNPs in 10 genes previously associated with NAFLD and the innate immune response and correlated the genotypes with liver fibrosis and fat accumulation. Results: Multinomial logistic regression analysis identified three metabolic parameters that were significantly associated with advanced liver fibrosis (stage F3–F4): albumin [odds ratio (OR) 0.80, 95% confidence interval (CI) 0.69–0.91, P = 0.001], percentage of visceral fat area (PVFA) (OR 1.06, 95% CI 1.01–1.12, P = 0.03) and BMI (OR 1.47, 95% CI 1.22–1.77, P < 0.0001). After adjustment for sex, albumin, PVFA and BMI, we found that three SNPs were significantly associated with advanced fibrosis, one each in PNPLA3/rs738409 ( P = 0.016), ADAR-1/rs1127313 ( P = 0.029) and IFIH1/rs1990760 ( P = 0.033). Conclusion: Our results indicate that genotyping for these SNPs can be a useful predictive tool for liver fibrosis progression and liver fat accumulation in patients co-infected with HIV-1/HCV.